"A team working together to make a big, nice, sound": An action research pilot study in an inclusive college setting. (September 2017) - Schwantes, Melody; Rivera, Eliana
Highlights: College students with intellectual disabilities may benefit from group music therapy. Community music therapy helps create authentic community for college students. Music therapy programs support college students with ID as part of clinical training. Abstract: A community music therapy approach was evaluated for students with and without intellectual and developmental disabilities (IDD) in a university setting with a postsecondary education program specifically designed for students with IDD. Action research was used to create space for social critique and reflexivity throughout the research process. The aim of the group approach was to establish community and relationships within the shared residence hall. Ten weekly sessions were held, and two performances were attended. Analysis of session notes, the researcher's journal, and interview transcripts revealed a series of themes. The participants identified ways that community was enhanced through the program and also highlighted some of the challenges they experienced. The results indicated that community music therapy can provide an authentic relationship building experience for college students in an inclusive setting. Limitations and recommendations for future research and clinical work are included.